FIRM VALUE IMPACT OF INTELLECTUAL CAPITAL, COMPANY SIZE, PROFITABILITY, CAPITAL STRUCTURE AND ASSETS STRUCTURE - Dede Hertina; 2Leo Lita Mayasari; Fransisca Rina Sulandari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the effect of Intellectual Capital, Company Size, Profitability, Capital Structure, Asset Structure on Firm Value in Crude Oil and Gas Sub-Sector companies listed on the Indonesia Stock Exchange for the period 2013 - 2018. This research method uses panel data regression analysis method. The population of this study is the Crude Oil and Natural Gas Sub-Sector companies listed on the Indonesia Stock Exchange for the period 2013-2018 with a total sample of 7 companies. The results of the study state that intellectual capital affects firm value, firm size does not affect firm value, profitability affects firm value, capital structure affects firm value and asset structure does not affect firm value.